2019
DOI: 10.1029/2018ja026414
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of Radiation Belt Modeling

Abstract: The “Quantitative Assessment of Radiation Belt Modeling” focus group was in place at Geospace Environment Modeling from 2014 to 2018. The overarching goals of this focus group were to bring together the current state‐of‐the‐art models for the acceleration, transport, and loss processes in Earth's radiation belts; develop event‐specific and global inputs of wave, plasma, and magnetic field to drive these models; and combine all these components to achieve a quantitative assessment of radiation belt modeling by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 62 publications
0
20
0
Order By: Relevance
“…Literature reviews can be found in Schulz (), Li and Temerin (), Friedel et al (), Millan and Thorne (), Shprits et al (, ), Reeves et al (), Thorne et al (), Millan and Baker (), and Baker et al (). We also recommend the discussions in Summers (), Baker et al (), Liemohn and Chan (), Denton et al (), Liemohn et al (), Lanzerotti and Baker (), Tu et al (), and Yu et al ().…”
Section: Introductionmentioning
confidence: 98%
“…Literature reviews can be found in Schulz (), Li and Temerin (), Friedel et al (), Millan and Thorne (), Shprits et al (, ), Reeves et al (), Thorne et al (), Millan and Baker (), and Baker et al (). We also recommend the discussions in Summers (), Baker et al (), Liemohn and Chan (), Denton et al (), Liemohn et al (), Lanzerotti and Baker (), Tu et al (), and Yu et al ().…”
Section: Introductionmentioning
confidence: 98%
“…Like the two previous models, this model also accounts for losses due to hiss interactions inside the plasmasphere and due to chorus interactions outside the plasmapause. The bounce‐averaged electron pitch angle diffusion coefficients were calculated using the University of California, Los Angeles Full Diffusion Code (Ni et al, , ; Shprits & Ni, ) and made available by the QARBM GEM focus group (Tu et al, ). The model of pitch angle diffusion coefficients due to scattering by plasmaspheric hiss was derived using the global distribution of the hiss frequency spectrum and wave intensity obtained from Van Allen Probes observations (Li et al, ), as well as the wave normal angle distribution from Ni et al ().…”
Section: Instrumentation and Model Descriptionmentioning
confidence: 99%
“…The pitch angle scattering by wave-particle interactions with magnetospheric plasma waves, which violates all three adiabatic invariants, contributes to the permanent loss of electrons to the atmosphere. For electrons in the range of 50-600 keV in this typical CIR event, although electron fluxes all returned to the average value during the recovery phase, many studies have shown that the recovery of electron flux during magnetic storms is not a purely adiabatic process and the role of nonadiabatic process could be investigated by converting fluxes to phase space density (e.g., Tu et al, 2019;Turner et al, 2012Turner et al, , 2013. So more research on phase space density (PSD) as a function of three adiabatic invariants is needed to study the relative role that loss to the magnetopause and precipitation to the atmosphere played.…”
Section: Space Weathermentioning
confidence: 99%